Aplikasi Pengawasan Kepatuhan Minum Obat Pasien Tuberkulosis (TBC) berbasis Mobile - Erdian, Naufal; Rosika, Herliana; Widiartha, Ida Bagus Ketut (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
Based on WHO data from 2024, Indonesia ranks second after India as the country with the highest number of tuberculosis (TB) cases in the world. Low patient adherence to regular medication intake, caused by the weakness of manual monitoring systems by healthcare workers, remains a major challenge in TB control. This study aims to develop a mobile application to monitor tuberculosis treatment and improve patient medication adherence. The application was developed using a software engineering approach with the Personal Extreme Programming (PXP) method, involving stages of planning, design, implementation, and iterative testing. Data collection techniques included observation, structured interviews, and User Acceptance Testing (UAT) through an online Likert-scale-based questionnaire. The outcome of this study is a mobile-based application featuring medication reminders, daily consumption reporting, monitoring by healthcare workers, and the provision of educational information. Black-box testing results indicated that all application features functioned as intended, while UAT results showed that the application is user-friendly and supports healthcare workers in effectively monitoring patient treatment. These findings demonstrate that the application can serve as a digital solution to improve TB treatment adherence and strengthen medication monitoring systems, particularly in high-burden areas.